Налоговые льготы по НДС в странах Европы и основные причины их использования - Соколовская, Е.В. (Економіка промисловості, 2016)
Проанализированы причины использования сниженных ставок НДС, а также определены стандартные и льготные ставки НДС, которые используются на сегодняшний день в странах Европы. Проаналізовано причини використання скорочених ставок ПДВ, а також визначено стандартні та пільгові ставки ПДВ, які використовуються у країнах Європи на сьогоднішній день. The article examines the reasons for applying the reduced VAT rates; we defined two such motives, notably distributional considerations and presence of public and/or merit goods. We also determined that there are some factors influencing on efficiency of reduced VAT rates, notably passing through the lower rate in sales prices, elasticity of demand, which could be considered as main ones. Also these factors include the size of price reduction, signaling effects, product life cycles, level of price reduction, marketing, etc. The indirect influence of reduced VAT rates on economic efficiency appears principally due to cross-border transactions and opportunities to avoid and/or to evade VAT, arising as a result of use of appropriate incentives. Among other factors are rebound effect, innovation and market transformation, free-rider problem, and effects on state budget. We also briefly analyzed both administrative and compliance costs related to the application of reduced VAT rates and main reasons of their occurrence, such as existence of “mixed products”, etc. We examined the data on 28 European countries concerning both standard and reduced VAT rates in 2016. As a result we defined that currently the most common goods and services, covered by VAT incentives in EU countries, are basic foodstuffs; pharmaceutical products; medical equipment for disabled persons; books, newspapers, periodicals; hotel accommodation, restaurants; and public transport, admission to cultural and/or sport events, water supplies.